The Status of Occupational Protection During COVID-19 Pandemic: Knowledge, Attitudes, and Practice of Healthcare Workers in Endoscopy Units, China - Yuan Tian; Bixiao Nian; Yongchen Ma; Xinyue Guo; Feng Wang; Long Rong (Frontiers Media S.A., 2021)
Background: SARS-CoV-2 spreads rapidly around the world, and some patients present gastrointestinal symptoms. The existence of the virus in the gastrointestinal tract makes digestive endoscopy a high-risk operation, which associated with an increased risk of infection rate in healthcare workers. This study aimed at exploring current knowledge, practice and attitudes of healthcare workers in endoscopy units in China regarding the status of occupational protection during COVID-19 pandemic.Methods: A cross-sectional study of a national online survey involving 717 healthcare workers in endoscopy units from 94 medical structures in 24 provinces and municipalities around China was conducted online via a questionnaire platform called Wenjuanxing (wjx.cn). The data were analyzed using correlation approaches, Kruskal-Wallis test for independent samples, and linear regression models.Results: Most Chinese healthcare workers in endoscopy units had a good knowledge of COVID-19 (median: 10; range: 7-12), showed a strikingly positive attitude (median: 65; range: 39-65), and carried out good practice (median: 47; range: 14-50) in strengthening the protection, disinfection and management of COVID-19. In terms of attitudes, female staff was more concerned about protection against COVID-19 than male staff (KW = 8.146, P = 0.004). Nurses performed better in both attitude (KW = 2.600, P = 0.009) and practice (KW = 6.358, P < 0.001) than endoscopic physicians when carrying out personal protection, patient care and environmental disinfection against SARS-CoV-2 infection. More positive attitudes in protection were related to better protective behavior in endoscopic daily medical work (r = 0.312; P < 0.001).Conclusion: The findings of this study suggest that Chinese endoscopy healthcare workers have an excellent mastery of knowledge about COVID-19, which is transformed into positive beliefs and attitudes, contributing to good practice during daily endoscopic procedures. Medical staff may benefit from further education. With the gradual normalization amid the ongoing COVID-19 pandemic, protection and management in endoscopy units may be changed accordingly.